The Role of Environmental Organizations in Antarctic Treaty System: The Case of the Antarctic and Southern Ocean Coalition - Elçin DORUK (International Journal of Politic and Security, 2021)
The relationship between environmental organizations and states and intergovernmental organizations can be named as a strategic interaction in which states try to instrumentalize environmental organizations to gain superiority, and environmental organizations take over the functions previously held by states. In this regard, the role played by the Antarctic and Southern Ocean Coalition (ASOC), which consists of many environmental NGOs, in the politics of Antarctica evolved in time. The existence of the ASOC takes place in a broader framework of growing ecological concerns, the evolving legal tools to address them, and the development of the Antarctic Treaty System, which governs the continent. In this context, this study aims to analyze the relationship between ASOC and nation-states in the context of the Antarctic Treaty Consultation Meetings, which shape the system governing the continent. The methodology is mainly based on the evaluation of meeting reports, management plans, and policy documents in terms of quality and quantity. Environmental sensitivities increasing according to the expected result from the general structure highlight the effectiveness of ASOC in Antarctic affairs.